Atividade antioxidante, antimicrobiana e caracterização de compostos bioativos da casca interna de Kielmeyera coriacea Mart. & Zucc - Santana, Eder Cley (2017)
This work aims to provide information on the chemical constitution and evaluation of antimicrobial activity of ethanolic extract and fractions from the inner bark of Kielmeyera coriacea Mart & Zucc, a typical Cerrado tree and used as a medicinal plant. The study evaluated the antimicrobial and antifungal potential of ethanolic extract (EE) and partitions. Antibacterial activities study were analyzed using aerobic and anaerobic buccal bacteria by Microdiluition Method in broth, with the results expressed in minimum inhibitory concentrations (MIC). In this analysis, the n-hexane (HP) partition was the most active, presenting MIC values between 1.56 and 6.25 μg mL-1, and for the Streptococcus mitis and Streptococcus sanguinis bacteria values were better than those found for amphotericin (CIM 3.688 μg mL-1), the drug used as positive control. These results awakened interest for the isolation of compounds. The tests with fractions of n-hexane partition showed a decrease of this activity with MIC values between 12.5 and 1500μg mL-1. These results may be relates to compounds that were acting synergistically and separated during the fractionation on column. In evaluating the antifungal potential against the yeasts of the genus Candida, both the extract and partitions inhibited the growth of all species tested, with minimum inhibitory concentrations (MIC) varying from 23.43 and 1500 μg mL-1, being the partitions dichloromethane and n-butanol that presented the most promising values, at concentrations between 23.43 and 46.87 μg mL-1. The antioxidant activity evaluated by the DPPH free radical method and by the electrochemical method. The Effective Concentration (EC50) values were better for the ethyl acetate (AP) and n-butanol (BP) partitions (between 2.0 and 1.6 μg mL-1, respectively), and lower than the BHT control (4.8 μg mL-1). The antioxidant activity confirmed in the electrochemical method. These results are in accordance with the highest levels of phenolic compounds present in these partitions. Phytochemical screening also revealed the presence of phenolic compounds (tannins, xanthones, coumarins, flavonoids and saponins), as well as terpenes and terpenoids. In the n-hexanic partition identified by Gas Chromatography coupled to Mass Spectrometry and by Nuclear Magnetic Resonance the steroids β-sitosterol, stigmasterol, campesterol and sitost-4-en-3-one, the triterpenes α-amirin and lupeol and the fatty acid hexadecanoic. The presence of these compounds in the n-hexane partition may explain the strong antibacterial activity, since these compounds act in the inhibition against different microorganisms, including the buccal ones. The analysis of ethanolic extract and more polar partitions polarity by High Performance Liquid Chromatography coupled to Mass Spectrometry with Electrospray Ionization in negative and positive modes have been identified protocatecuic acid, flavonoid epi-catechin and proanthocyanidins A, B, C type and its oligomers. In the partition n-butanol was identified a dimer of epi-catechin-epi-gallocatechin and gallocatechin-3-O-glycoside; on partition ethyl acetate and methanol-water residue has been identified the dimer epi-afzelequin-epi-catechin. The identification of these phenolic compounds in polar partitions can explain the results of antioxidant and antifungal activity. This study indicates that the inner bark of Kielmeyera coriacea Mart & Zucc is rich in bioactive compounds, exhibiting biological activity against oral bacteria and fungi. Keywords: Kielmeyera coriacea Mart & Zucc. Extract and partitions. Biological activities.